Biodegradable polymers for sustainable PCBs - Soumya (RSYN Proceedings, 2025)
The printed circuit board (PCB), serving as an intermediary between physical components and intricate electrical designs, physically supports and connects various electronic devices for constructing sophisticated systems. Among all commonly used substrates for both insulation and structural integrity within printed circuit boards, FR4, which is a composite of fibreglass reinforced in a polymer matrix, is unique and used on a large scale. It exhibits high strength and rigidity, high melting point and low moisture absorption, which makes it perfect for PCB designing. However, with rising global e-waste levels, the disposal of PCBs poses significant challenges, as they are harmful to the environment, difficult to recycle, and resource-intensive. Conventional methods for recycling components in PCBs often exhibit poor efficacy due to demanding procedures like thermal treatments and intense pressures. Thus, eco-friendly alternatives such as polylactic acid (PLA) and polyhydroxybutyrate (PHB) are explored in this work. These two polymers are not only 100% biodegradable and compostable but also easy to mold and print, and are resistant to many organic solvents. However, these two biopolymers find application in low-power circuits owing to their low melting points of about 130–180 ◦C for PLA, and 170–180 ◦C for PHB, respectively, so they cannot withstand the high-temperature soldering process (up to 260 ◦C). Thus, these polymers lack adequate thermal insulation, resulting in diminished structural integrity and increased susceptibility to moisture ingress relative to standard FR-4 substrate material. This review involves a comparative analysis based on existing research studies focusing on the mechanical and thermal performances of PLA and PHB. The objective of this study is to show that by combining PLA and PHB with additives such as cellulose nanocrystals to improve thermal resistance, along with fibres like jute or hemp for enhanced tensile properties and glass/carbon fibres for increased stiffness and reduced water absorption, this composite material could serve as an environmentally friendly substitute for conventional FR-4 circuit boards in applications requiring significant electrical conductivity.
Keywords: Polylactic acid (PLA), Polyhydroxybutyrate (PHB); Printed Circuit Boards (PCBs), flame-retardant-4 (FR4)